2016
DOI: 10.1136/jfprhc-2016-101481
|View full text |Cite
|
Sign up to set email alerts
|

Reusable sanitary towels: promoting menstrual hygiene in post-earthquake Nepal

Abstract: Abstract:It is a normal human tendency to run for their life when an earthquake occurs. Adolescent girls and reproductive age women leave their homes with only the clothes they had on trying to save their own and their families' lives. Immediate disaster relief aid with its (unintentional) lack of gender sensitivity has little or no materials for the appropriate management of menstrual hygiene.The biological needs will not change for these women despite the dire need for basic food, shelter and security. Timel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…A document provided by the United Nations Population Fund 29 was found succinctly to outline culturally appropriate MH items for distribution in the Myanmar context, as well as considerations for method of distribution and hygiene-promotion activities. Budhathoki et al 21 suggested using a local menstrual kit in Nepal that contained four pieces of cotton cloth, two undergarments, and one bar of soap sealed in a biodegradable bag.…”
Section: Resultsmentioning
confidence: 99%
“…A document provided by the United Nations Population Fund 29 was found succinctly to outline culturally appropriate MH items for distribution in the Myanmar context, as well as considerations for method of distribution and hygiene-promotion activities. Budhathoki et al 21 suggested using a local menstrual kit in Nepal that contained four pieces of cotton cloth, two undergarments, and one bar of soap sealed in a biodegradable bag.…”
Section: Resultsmentioning
confidence: 99%
“…Immediate measures during disasters are considered possible using locally available cloth as adsorbents [ 13 ]. The efforts need to emphasize the need for private spaces for women focusing on menstrual hygiene management apart from the toilets.…”
Section: Discussionmentioning
confidence: 99%
“…On 25 th April 2015, Nepal was affected by a 7.8 Richter scale magnitude earthquake killing almost 9000 people and displaced 3.5 million people [ 25 ]. Compared to men, more women survived [ 26 ] and although emergency relief and rescue operations swiftly began addressing essential humanitarian needs, there seemed to be a lack of attention to menstrual hygiene needs of adolescent girls and women [ 13 , 27 ]. Although increasingly considered, menstrual hygiene continues to be overlooked during disasters, even in community level responses [ 22 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An article in this issue of the journal highlights one easily forgotten hardship among many faced by women in this situation. Budhathoki and coworkers describe the difficulties surrounding menstrual hygiene in post-earthquake Nepal, where women used and reused clothes as sanitary towels – a practice that was considered culturally acceptable and feasible in crisis situations 1. The authors argue that menstrual hygiene received a low priority due to the overwhelming need of water, food and shelter in such crisis situations.…”
mentioning
confidence: 99%